Analisa Perbandingan Pengaruh Penggunaan Protokol Secure Soket Layer (SSL) Dan Protokol Point To Point Protocol (PTTP) Terhadap Quality Of Service (QoS) Pada Jaringan Vitual Private Network (VPN) - Lamhot Raden Sitorus; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Security Protocols Protocol Point-to-Point (PPTP) and Secure Socket Layer (SSL) are VPN security protocols that used to enhance the security of a network. The use of these protocols effect on performance network or Quality of Service (QoS). The QoS is measured using delay parameters, the jitter, throughput, and packet loss. Network testing scenario uses the topology bus. The results of this research is to compare the performance of each VPN protocols tested i.e. PPTP and SSL in a way of measuring the QoS performance without using the Protocol as a basis for comparing its effects byusing VPN protocols.Keywords : Virtual Private Network, PPTP, SSL, Quality of Services